Excitation-transcription coupling via synapto-nuclear signaling triggers autophagy for synaptic turnover and long-lasting synaptic depression. Issue 11 (2nd November 2021) - Pan, Yue; Zhou, Guangjun; Li, Wenwen; He, Xingzhi; Li, Cuicui; Li, Yanjun; Li, Tao; Hu, Hailan; Ma, Huan
ABSTRACT: For network rewiring and information storage in the brain, late phase long-term synaptic depression (L-LTD) requires the long-lasting reorganization of cellular resources. We found that activation of GRIN/NMDAR recruits transcription-dependent autophagy for synaptic turnover to support L-LTD. Activity-dependent CRTC1 synapto-nuclear translocation increases nuclear CRTC1 that competes with FXR for binding to CREB; this in turn enhances the direct binding between CRTC1-CREB and macroautophagy/autophagy gene promoters. Synergistic actions of CRTC1-CREB are preferentially turned on by LTD-inducing stimuli and switched off by genetic knockdown of CREB or CRTC1, or acutely activating FXR. Disrupted CRTC1-CREB signaling impairs activity-driven loss of surface GRIA/AMPARs and DLG4/PSD-95, and selectively prevents GRIN/NMDAR-dependent L-LTD, which are rescued by enhancing MTOR-regulated autophagy. These findings suggest a novel mechanism in L-LTD, in which brief synaptic activities recruit long-lasting autophagy through excitation-transcription coupling for ensuing synaptic remodeling.